Changes in electrical conductivity of liquid foods during ohmic heating - Srivastav, Shivmurti; Roy, Srishti (International Journal of Agricultural and Biological Engineering, 2014)
Ohmic heating is a food processing method in which alternating current (AC) went through a food sample and resulted in internal energy generation in foods. It is an alternative fast heating technique. Its principal advantage is the ability to rapidly and uniformly heat food materials of various densities. During ohmic heating, change in electrical conductivity was observed. The intensity of food materials’ electrical conductivity or overall resistance critically controls ohmic heating rate. An ohmic heating set-up was prepared under this project. Tomato juice was heated (about 32℃ to 80℃) in a batch type ohmic heater at different voltage gradients in the range of 50–70 V/cm. It was statistically found that the voltage gradient had significant impact on conductivity and system performance coefficient (SPC) (P less than 0.05). It was concluded that the electrical conductivity values linearly increased with temperature. The SPCs of the system ranged between 0.779 and 0.943. The value of R2 of the linear model was greater than 0.98. Keywords: ohmic heating, electrical conductivity, thermal conductivity, liquid foods DOI: 10.3965/j.ijabe.20140705.015 Citation: Srivastav S, Srishti R. Changes in electrical conductivity of liquid foods during ohmic heating. Int J Agric & Biol Eng, 2014; 7(5): 133－138.